Perceived and preferred interviewer characteristics in selection interview - Marzuki, Najib Ahmad (Canadian Center of Science and Education, 2013)
Perceptions of interviewer characteristics signify the validity and reliability of selection procedures.Personality characteristics of the interviewer such as personableness, skills and competency, questioning manner and job information may be perceived differently in different situations. This study examined the perceived and preferred interviewer characteristics based on Perceived Interviewer Characteristics Scale by Ahmad Marzuki (2000).In addition, it included the preferred interviewer characteristics scales modified from the original scales.A total of 140 participants were selected as samples.Results indicated that the actual 4 scales except for ‘questioning manner’ characteristic were correlated to the preferred interviewer characteristics.Results also shown that there were significant differences between what the applicants perceived and what the applicants preferred in three interviewer characteristics namely personableness, skills and competency and job information in general, as well as based on those who were offered and not offered the job.